Surgical Site Infection among Women Post Cesarean Section: An Integrative Review - Novelia, Shinta; Sae Sia, Wipa; Songwathana, Praneed (Nurse Media Journal of Nursing, 2017)
Background: Surgical site infection (SSI) in cesarean section (CS) is a major cause of prolonged hospital stay and resource consumption, and causes morbidity and mortality for the mother and the baby.Purpose: This literature review aimed to assess and identify risk factors, interventions, and prevention strategies of SSI for women post CS especially the obese women.Methods: An integrative literature review was conducted by employing the databases of PubMed, ProQuest, Science Direct, Wiley online library, and Google scholar from 1999 to 2015. This review identified the studies conducted either in women post-CS or obese women post CS.Results: A total of 58 articles were found, and 14 articles met the criteria. The risk factors of CS-SSI were classified into extrinsic and intrinsic factors. The intrinsic factors include limited mobility, poor nutrition, and comorbidity (diabetes) while the extrinsic factors include surgical technique, skin closure methods, prophylactic antibiotic, and the use of drains. Poor nutrition, diabetes, and limited mobility were the common factors found in obese women undergoing CS. Maintaining nutritional status and controlling blood glucose were proposed to prevent CS-SSI among obese women post-CS.Conclusions: Nurses should have adequate knowledge about the risk factors of CS-SSI to assess the risk factors of CS-SSI especially in obese women. The intervention of CS-SSI might need a bundle of interventions which consist of pre-operative and post-operative prevention strategies.